Adolescent nutrition in West Africa: A rapid review of the research evidence - Verstraeten, Roosmarijn; Salm, Leah; Diop, Loty; Diatta, Ampa Dogui; Touré, Mariama (International Food Policy Research Institute, 2020)
Adolescence is an important period of physical and cognitive development during which optimal nutrition is crucial. It is an essential time for forming preferences and habits and a key window of opportunity for influencing adult health. In West Africa, while undernutrition rates remains high, there has also been a steady rise in overweight and obesity, and an increasing share of mortality and morbidity due to diet-related noncommunicable diseases (DR-NCDs) among adolescents. f concern is that adolescents are experiencing these diseases earlier in life than previous generations. It is crucial to address adolescents’ nutrition to prevent them from carrying malnutrition into adulthood and to protect their overall health later in life.